2013
DOI: 10.1111/jai.12314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Saccharomyces cerevisiae supplementation on immune response, hematological parameters, body composition and disease resistance in rainbow trout, Oncorhynchus mykiss (Walbaum, 1792)

Abstract: Summary Natural substances are now generally preferred over chemical and synthetic compounds for the growth and immune enhancement of aquatic organisms. The aim of this study was to evaluate the effect of Saccharomyces cerevisiae extract and hydrolyzed powder on immunity, hematological parameters and body composition in rainbow trout, Oncorhynchus mykiss. Six hundred rainbow trout (50 ± 5 g mean weight) were acclimated to laboratory conditions and then randomly divided into four groups of triplicate tanks. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…There are few data on effects of processing on digestibility, and whether different yeasts require different processing methods. It has been suggested that the thick and rigid cell walls are a major problem inhibiting industrial production and utilisation of dietary yeast protein . A poorly digestible cell wall may limit enzymatic access to cellular contents, depending on yeast cell characteristics as well as growth substrate and processing conditions.…”
Section: Digestibility Of Yeast In Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few data on effects of processing on digestibility, and whether different yeasts require different processing methods. It has been suggested that the thick and rigid cell walls are a major problem inhibiting industrial production and utilisation of dietary yeast protein . A poorly digestible cell wall may limit enzymatic access to cellular contents, depending on yeast cell characteristics as well as growth substrate and processing conditions.…”
Section: Digestibility Of Yeast In Fishmentioning
confidence: 99%
“…Various chemical, enzymatic, physical or mechanical methods can be used to rupture the yeast cell walls (reviewed by Nasseri et al ). Digestibility of yeast nutrients can be increased by mechanical rupturing of cell walls or enzymatic hydrolysis . Enzymatic pre‐treatment followed by high‐pressure mechanical homogenisation have been shown to be efficient for C. utilis .…”
Section: Digestibility Of Yeast In Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with those of Li et al (2005) concluded that dietary supplemented diet of Juvenile red drum (Sciaenops ocellatus) with Brewer's yeast (S. cerevisiae) did not promote resistance to handling stress. Many studies however, show greater resistance to salt stress (Pooramini et al, 2014) or pathogens challenge (Chiu et al, 2010;Tukmechi and Bandboni, 2014;).…”
Section: Discussionmentioning
confidence: 97%
“…However, one problem of using yeast in the diet is the low digestibility of the yeast cell walls. Digestibility of the yeast can be increased through enzymatic hydrolysis, during which a high volume of nucleic acids is released (Tukmechi and Bandboni, 2014).…”
Section: Discussionmentioning
confidence: 99%